Spatial distribution and statistical analysis of tourism products in the Lattakia region. - ناصر, لميس (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The geographical distribution of tourism products is considered on of the most important tourism studied due to its very close connection with tourism development, As it contributes to its diversity in the prosperity, and growth of tourism, The lattakia regon is considered one of the most important tourist areas of the lattakia covernorate due to its richness in tourism products, which is an important economic resource that’s must be developed due to its attractivenesse to local tourists,in light of the lack of foreign tourism movement as aresult of the war that Syria was exposed to, through this research, astudy was carried out impotance, properties tourism products, and astudy of their diversity and geographical distribution in the lattakia region were studied, and the tourism activity was studied statistically using the spss.25 program, and the chi-square test, and the descriptive analysis was studied, and the geographical distribution index of tourism products was studied, and the researcher reached through the questionnaire and statistical analysis that there is an important relationship statistically between the age of the tourists, and the type of tourism product they go to, as the composite tourism product occupies the forefront of tourist distinations by 40%, and the direction of the geographical distribution of tourism products spreads in a longitudinal, slanting manner towards the northwest of the region.